2013
DOI: 10.7554/elife.01086
|View full text |Cite
|
Sign up to set email alerts
|

Essential yet limited role for CCR2+ inflammatory monocytes during Mycobacterium tuberculosis-specific T cell priming

Abstract: Defense against infection by Mycobacterium tuberculosis (Mtb) is mediated by CD4 T cells. CCR2+ inflammatory monocytes (IMs) have been implicated in Mtb-specific CD4 T cell responses but their in vivo contribution remains unresolved. Herein, we show that transient ablation of IMs during infection prevents Mtb delivery to pulmonary lymph nodes, reducing CD4 T cell responses. Transfer of MHC class II-expressing IMs to MHC class II-deficient, monocyte-depleted recipients, while restoring Mtb transport to mLNs, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 24 publications
12
153
0
1
Order By: Relevance
“…CCR2 ϩ monocytes, on the other hand, have been implicated in defense against intracellular pathogens, including Listeria monocytogenes, Mycobacterium tuberculosis, and Toxoplasma gondii, although they also contribute to clearance of the fungal pathogen Aspergillus fumigatus (21,23,38,39). As a small subset of blood circulating cells with remarkable plasticity, CCR2…”
Section: Discussionmentioning
confidence: 99%
“…CCR2 ϩ monocytes, on the other hand, have been implicated in defense against intracellular pathogens, including Listeria monocytogenes, Mycobacterium tuberculosis, and Toxoplasma gondii, although they also contribute to clearance of the fungal pathogen Aspergillus fumigatus (21,23,38,39). As a small subset of blood circulating cells with remarkable plasticity, CCR2…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage depletion studies around the time of aerosol challenge, however, revealed that lung-resident AMs and not CCR2-dependent myeloid cells, such as inflammatory monocytes/macrophages (IMs), play an important role in establishment of infection and initial growth of bacteria (Leemans et al 2001;Samstein et al 2013). Moreover, elegant studies using adoptive transfer approaches of Mtb-infected AMs exposed an important early role for these cells not only in establishment of infection, but also in influencing initiation and priming of T-cell responses 2-3 wk later .…”
Section: Role Of Alveolar Macrophages In Early Events Of Mtb Infectionmentioning
confidence: 99%
“…Bone marrow-derived inflammatory monocytes recruited from the blood following signals from the chemokine (C-C motif) ligand 2 (CCL2) are essential for controlling lung infections (14)(15)(16)(17). Although CY significantly depleted Ly-6C hi monocytes from the whole lung (Fig.…”
Section: Lung Macrophages Are Required For the Vaccine-induced Protecmentioning
confidence: 99%